Child maltreatment, social capital, maternal mental health and duration of program involvement: Assessment from a community-based empowerment program in Kenya - Goodman, Michael L. (Journal of family violence, 2023)
Multisystem, multi-level interventions are required to enable resilient, nurturing environments for children facing adversity. This study assesses parenting behavior associated with participation in a community-based, adapted microfinance program, and mediated by program-affiliated social capital, maternal depression and self-esteem among Kenyan women. Participants in the intervention, Kuja Pamoja kwa Jamii (KPJ, Swahili for “Come Together to Belong”), gather weekly to engage in trainings and group-based microfinance. Groups selected for the study had participated in the program for 0–15 months at the time of the first interview. Women (n = 400) completed surveys in June 2018 and June 2019. Measures included duration of program exposure, group-affiliated social capital (i.e. trust, belonging, cohesion, and expectation of mutual benefit), depression, self-esteem, and conflict tactics. We used regression analyses and generalized structural equation models to explore associations between program exposure, social capital, psychosocial variables and child maltreatment. Each standard deviation increase in duration of program exposure decreased odds of child physical abuse by 40% and child neglect by 35%. Each standard deviation in the social capital index predicted a significant reduction in odds of child physical abuse (aOR: 0.67), and child neglect (aOR: 0.71). Self-esteem and depression fully mediated observed associations between social capital and child maltreatment. Findings recommend further investigation of the potential for adapted microfinance programs to deliver parenting interventions, improve mental health and foster resilience-enabling social capital. A randomized control trial is required to validate the potential of the assessed intervention to improve parenting behaviors and supportive social conditions.